Unusual treatment for calcifying odontogenic cyst using decompression tube to prevent pathological fracture (Research, Society and Development, 2021)
The calcifying odontogenic cyst (COC) is an uncommon lesion, with variable clinical and histopathological behavior. The cystic form is the most frequent and the most common histological characteristic is the presence of a variable number of phantom cells in the epithelial component. The standard treatment for this injury is enucleation followed by curettage or excision. However, when other factors are associated, this single-step approach can lead to complications such as pathological fractures. A common treatment for keratocysts and dentigerous cysts, but uncommon for COC has been showing high effectiveness. Thus, a two-stage approach using a tubular object to perform initial decompression of the lesion and later excision of the lesion can be performed in order to prevent complications. Here we report a two-stage treatment, through initial surgical decompression, of a COC associated with a lower second molar in the mandibular basilar region, using a tubular device, in which a pathological fracture was prevented. The results of this case corroborate the use of decompression applied to the treatment of COC.